Kaasaegse udmurdi pulmatseremoonia eripära ja kultuuriline tähendus - Tatiana Korobova (Mäetagused)
This article aims to analyze the current state of Udmurt weddings. While remaining a vital tradition, their structure is undergoing changes. Customs and rituals that were originally intended to help participants adjust to new social roles are losing their symbolic significance. Many of these rituals are now seen as mere entertainment or have even disappeared altogether. At the same time, new customs and traditions are emerging, becoming an integral part of modern Udmurt weddings and forming a new type of celebration with its own unique characteristics. These new customs are becoming increasingly popular and are now considered traditional in modern society.